A PERCEPTION OF FEAR - Yazid, Rizky; Bakhtiar, Amsal (ILMU USHULUDDIN, 2024)
This research departs from the empirical-epistemological fact that there are ideas about fear stored in memory that do not originate from any experience. This fact is based on data that researchers obtained through observations of people who are fear of heights and depths of water. From these empirical facts, two basic assumptions result, firstly, the idea of fear comes from impulses in the mind itself before experiencing it. Second, the idea of fear comes from sensations or impressions after experiencing it. From the differences between these two basic assumptions, there has also become an academic debate around epistemologies that separates Cartesian rationalism and Humean empiricism. For the Cartesian group, ideas originate from consciousness (cogito) as part of the activity and impulse of the mind so that the truth is clear and distinct. This means that the ideas in the mind itself are clear and distinct. Meanwhile, for the Humean group, ideas originate from copies of certain impressions as part of experience activities so that they are clearer and more alive. This means that ideas in the mind themselves are vague because they are copies of impressions. From the academic debate between the two major groups in the philosophy of knowledge, which helps researchers to clarify the idea of fear stored in memory.